2018
DOI: 10.1002/nop2.232
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation of the experience of participation in Mindfulness‐based Intervention for IVF‐ET (MBII) with Chinese women undergoing first IVF‐ET

Abstract: Aim To explore what the women experience during their first IVF‐ET treatment while participating a mindfulness‐based intervention for IVF‐ET (MBII), and how they use it to enhance their infertility‐related quality of life (QoL). Design Qualitative exploratory design. Methods As part of a larger multimethod study, this study shares the description from 38 IVF‐ET women. We conducted semi‐structured interviews and collected daily practice diary.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…A systematic review of the literature revealed that participants who had mind-body interventions had reduced anxiety traits and depression scores though the reduction was of low or moderate amplitude in most studies (Gaitzsch, et al 2020) suggested improvements may occur in distress ratings and pregnancy rates for women experiencing infertility (Clifton et al, 2020). According to the findings of Li et al (2018) awareness, control over life and acceptance may be potential mechanisms that lead to improved infertility-related Quality of Life (QoL) in women following mind and body intervention programme. This ultimately improves the treatment's effectiveness.…”
Section: Influence Of Psychological Distress On Infertility Treatmentmentioning
confidence: 99%
“…A systematic review of the literature revealed that participants who had mind-body interventions had reduced anxiety traits and depression scores though the reduction was of low or moderate amplitude in most studies (Gaitzsch, et al 2020) suggested improvements may occur in distress ratings and pregnancy rates for women experiencing infertility (Clifton et al, 2020). According to the findings of Li et al (2018) awareness, control over life and acceptance may be potential mechanisms that lead to improved infertility-related Quality of Life (QoL) in women following mind and body intervention programme. This ultimately improves the treatment's effectiveness.…”
Section: Influence Of Psychological Distress On Infertility Treatmentmentioning
confidence: 99%
“…4 Infertility problems affect mental health ranging from 25% to 60% of sufferers worldwide. 5 The prevalence of depression or mental health problems among infertile or infertile women is 28.03% in high-income countries and 44.32% in low- and middle-income countries. 6 They suffered from mental health such as stress, anxiety, depression, frustration, identity disorder, a lack of attractiveness, sexual satisfaction, and dysfunction.…”
Section: Introductionmentioning
confidence: 99%